Innovation and labour productivity in the Swiss manufacturing sector: An analysis based on firm panel data - Spyros Arvanitis (ETH Zurich, KOF Swiss Economic Institute, 2006)
This paper investigates (a) the determinants of innovation performance and (b) the impact of innovation performance on labour productivity of Swiss manufacturing firms in the period 1994-2002. The data used in this study come from the KOF panel database and were collected in 1996, 1999 and 2002 respectively based on a questionnaire quite similar to that used in the Community Innovation Surveys (CIS). The use of a wide spectrum of indicators helps to test the robustness of the specification of the innovation equation as well as the robustness of the impact of innovation on economic performance. We find a clear-cut positive effect of innovation on labour productivity.
Keywords: O30; 330; innovation; labour productivity; R&D expenditures; Innovation; Industrielle Forschung; Schweiz